![\int{\frac{x}{x^3-1}dx}=\int{\frac{x}{(x+1)(x^2+x+1)}dx} \int{\frac{x}{x^3-1}dx}=\int{\frac{x}{(x+1)(x^2+x+1)}dx}](https://tex.z-dn.net/?f=%5Cint%7B%5Cfrac%7Bx%7D%7Bx%5E3-1%7Ddx%7D%3D%5Cint%7B%5Cfrac%7Bx%7D%7B%28x%2B1%29%28x%5E2%2Bx%2B1%29%7Ddx%7D)
Разложим на слагаемые
\\=>x=A(x^2+x+1)+(Bx+C)(x-1);\\x=Ax^2+Ax+A+Bx^2-Bx+Cx-C=(A+B)x^2+(A-B+C)x+A-C=>\\=>\left \{ {{A+B=0} \atop {A-B+C=1}}\atop{A-C=0} \right.\left \{ {{A=-B} \atop {A-B+C=1}}\atop{A=C} \right.;\left \{ {{-B-B+C=1} \atop {-B-C=0}} \right.;-3B=1;B=-\frac{1}{3}=>A=C=\frac{1}{3}" alt="\frac{x}{(x+1)(x^2+x+1)}=\frac{A}{x-1}+\frac{Bx+C}{x^2+x+1}=\frac{A(x^2+x+1)+(Bx+C)(x-1)}{(x-1)(x^2+x+1)}=>\\=>x=A(x^2+x+1)+(Bx+C)(x-1);\\x=Ax^2+Ax+A+Bx^2-Bx+Cx-C=(A+B)x^2+(A-B+C)x+A-C=>\\=>\left \{ {{A+B=0} \atop {A-B+C=1}}\atop{A-C=0} \right.\left \{ {{A=-B} \atop {A-B+C=1}}\atop{A=C} \right.;\left \{ {{-B-B+C=1} \atop {-B-C=0}} \right.;-3B=1;B=-\frac{1}{3}=>A=C=\frac{1}{3}" align="absmiddle" class="latex-formula">
Запишем данный интеграл, как сумму интегралов
![\int{\frac{x}{(x+1)(x^2+x+1}dx}=\frac{1}{3}\int{\frac{1}{x-1}dx}+\int{\frac{-\frac{1}{3}x+\frac{1}{3}}{x^2+x+1}dx} \int{\frac{x}{(x+1)(x^2+x+1}dx}=\frac{1}{3}\int{\frac{1}{x-1}dx}+\int{\frac{-\frac{1}{3}x+\frac{1}{3}}{x^2+x+1}dx}](https://tex.z-dn.net/?f=%5Cint%7B%5Cfrac%7Bx%7D%7B%28x%2B1%29%28x%5E2%2Bx%2B1%7Ddx%7D%3D%5Cfrac%7B1%7D%7B3%7D%5Cint%7B%5Cfrac%7B1%7D%7Bx-1%7Ddx%7D%2B%5Cint%7B%5Cfrac%7B-%5Cfrac%7B1%7D%7B3%7Dx%2B%5Cfrac%7B1%7D%7B3%7D%7D%7Bx%5E2%2Bx%2B1%7Ddx%7D)
Посчитаем эти интегралы
![1)\frac{1}{3}\int{\frac{1}{x-1}dx}=\frac{1}{3}\ln(|x-1|)+C\\2)\int{\frac{-\frac{1}{3}x+\frac{1}{3}}{x^2+x+1}dx}=\begin{vmatrix}Px+Q=(x^2+x+1)'=\\=-\frac{1}{6}(2x-2)\end{vmatrix}=-\frac{1}{6}\int{\frac{2x-2}{x^2+x+1}dx}=-\frac{1}{6}\int{\frac{d(x^2+x+1)}{x^2+x+1}}+\frac{1}{2}\int{\frac{1}{x^2+x+1}dx(1)}=-\frac{1}{6}\ln(x^2+x+1)+\frac{2}{\sqrt{3}}\arctan(\frac{2(x+\frac{1}{2})}{\sqrt{3}})+C 1)\frac{1}{3}\int{\frac{1}{x-1}dx}=\frac{1}{3}\ln(|x-1|)+C\\2)\int{\frac{-\frac{1}{3}x+\frac{1}{3}}{x^2+x+1}dx}=\begin{vmatrix}Px+Q=(x^2+x+1)'=\\=-\frac{1}{6}(2x-2)\end{vmatrix}=-\frac{1}{6}\int{\frac{2x-2}{x^2+x+1}dx}=-\frac{1}{6}\int{\frac{d(x^2+x+1)}{x^2+x+1}}+\frac{1}{2}\int{\frac{1}{x^2+x+1}dx(1)}=-\frac{1}{6}\ln(x^2+x+1)+\frac{2}{\sqrt{3}}\arctan(\frac{2(x+\frac{1}{2})}{\sqrt{3}})+C](https://tex.z-dn.net/?f=1%29%5Cfrac%7B1%7D%7B3%7D%5Cint%7B%5Cfrac%7B1%7D%7Bx-1%7Ddx%7D%3D%5Cfrac%7B1%7D%7B3%7D%5Cln%28%7Cx-1%7C%29%2BC%5C%5C2%29%5Cint%7B%5Cfrac%7B-%5Cfrac%7B1%7D%7B3%7Dx%2B%5Cfrac%7B1%7D%7B3%7D%7D%7Bx%5E2%2Bx%2B1%7Ddx%7D%3D%5Cbegin%7Bvmatrix%7DPx%2BQ%3D%28x%5E2%2Bx%2B1%29%27%3D%5C%5C%3D-%5Cfrac%7B1%7D%7B6%7D%282x-2%29%5Cend%7Bvmatrix%7D%3D-%5Cfrac%7B1%7D%7B6%7D%5Cint%7B%5Cfrac%7B2x-2%7D%7Bx%5E2%2Bx%2B1%7Ddx%7D%3D-%5Cfrac%7B1%7D%7B6%7D%5Cint%7B%5Cfrac%7Bd%28x%5E2%2Bx%2B1%29%7D%7Bx%5E2%2Bx%2B1%7D%7D%2B%5Cfrac%7B1%7D%7B2%7D%5Cint%7B%5Cfrac%7B1%7D%7Bx%5E2%2Bx%2B1%7Ddx%281%29%7D%3D-%5Cfrac%7B1%7D%7B6%7D%5Cln%28x%5E2%2Bx%2B1%29%2B%5Cfrac%7B2%7D%7B%5Csqrt%7B3%7D%7D%5Carctan%28%5Cfrac%7B2%28x%2B%5Cfrac%7B1%7D%7B2%7D%29%7D%7B%5Csqrt%7B3%7D%7D%29%2BC)
![(1)\\\int{\frac{1}{x^2+x+1}dx=\int\frac{dx}{(x+\frac{1}{2})^2+\frac{3}{4}}=\frac{2}{\sqrt{3}}\arctan(\frac{2(x+\frac{1}{2})}{\sqrt{3}})+C (1)\\\int{\frac{1}{x^2+x+1}dx=\int\frac{dx}{(x+\frac{1}{2})^2+\frac{3}{4}}=\frac{2}{\sqrt{3}}\arctan(\frac{2(x+\frac{1}{2})}{\sqrt{3}})+C](https://tex.z-dn.net/?f=%281%29%5C%5C%5Cint%7B%5Cfrac%7B1%7D%7Bx%5E2%2Bx%2B1%7Ddx%3D%5Cint%5Cfrac%7Bdx%7D%7B%28x%2B%5Cfrac%7B1%7D%7B2%7D%29%5E2%2B%5Cfrac%7B3%7D%7B4%7D%7D%3D%5Cfrac%7B2%7D%7B%5Csqrt%7B3%7D%7D%5Carctan%28%5Cfrac%7B2%28x%2B%5Cfrac%7B1%7D%7B2%7D%29%7D%7B%5Csqrt%7B3%7D%7D%29%2BC)
Объединяем решения
![\frac{1}{3}\ln(|x-1|)-\frac{1}{6}\ln(|x^2+x+1|)+\frac{1}{\sqrt{3}}\arctan(\frac{2x+1}{\sqrt{2}})+C=\\=\frac{1}{3}(]ln(]x-1|)-\frac{1}{2}\ln(x^2+x+1))+\frac{1}{\sqrt{3}}\arctan(\frac{2x+1}{\sqrt{2}})+C=\\=\frac{1}{3}\ln(\frac{|x-1|}{\sqrt{x^2+x+1}})+\frac{1}{\sqrt{3}}\arctan(\frac{2x+1}{\sqrt{2}})+C \frac{1}{3}\ln(|x-1|)-\frac{1}{6}\ln(|x^2+x+1|)+\frac{1}{\sqrt{3}}\arctan(\frac{2x+1}{\sqrt{2}})+C=\\=\frac{1}{3}(]ln(]x-1|)-\frac{1}{2}\ln(x^2+x+1))+\frac{1}{\sqrt{3}}\arctan(\frac{2x+1}{\sqrt{2}})+C=\\=\frac{1}{3}\ln(\frac{|x-1|}{\sqrt{x^2+x+1}})+\frac{1}{\sqrt{3}}\arctan(\frac{2x+1}{\sqrt{2}})+C](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%5Cln%28%7Cx-1%7C%29-%5Cfrac%7B1%7D%7B6%7D%5Cln%28%7Cx%5E2%2Bx%2B1%7C%29%2B%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%7D%5Carctan%28%5Cfrac%7B2x%2B1%7D%7B%5Csqrt%7B2%7D%7D%29%2BC%3D%5C%5C%3D%5Cfrac%7B1%7D%7B3%7D%28%5Dln%28%5Dx-1%7C%29-%5Cfrac%7B1%7D%7B2%7D%5Cln%28x%5E2%2Bx%2B1%29%29%2B%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%7D%5Carctan%28%5Cfrac%7B2x%2B1%7D%7B%5Csqrt%7B2%7D%7D%29%2BC%3D%5C%5C%3D%5Cfrac%7B1%7D%7B3%7D%5Cln%28%5Cfrac%7B%7Cx-1%7C%7D%7B%5Csqrt%7Bx%5E2%2Bx%2B1%7D%7D%29%2B%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%7D%5Carctan%28%5Cfrac%7B2x%2B1%7D%7B%5Csqrt%7B2%7D%7D%29%2BC)